Doodle Art 3D Model as an Effort to Reduce Patient Anxiety in Health Care Facilities - Rusyadi, Luthfi; Jeffri Ardiyanto,; Santoso , dan Bedjo (International Journal of Psychosocial Rehabilitation, 2020)
Background: Every individual who has a health problem, will try his best to overcome the problem of illness by seeking treatment at a health service facility or Fasilitas Pelayanan Kesehatan (fasyankes), but not all individuals dare to seek treatment at a health facility. This is caused by feelings of fear or anxiety of patients. One of the efforts made to reduce patient anxiety is to design health care facilities to be more attractive and not seem scary. An attractive environmental design in a health care facility is to provide three-dimensional picture messages on the walls of the patient's waiting room and/or examination room named "Doodle Art" as health promotion that also reduces patient anxiety. Purpose: Producing 3D Doodle Art models to reduce patient anxiety in health care facilities. Methods: The method used in this research is Research and Development (R&D) with stages: information gathering, model design, expert validation and revision as well as model testing (using the Quasi-Experimental Control Group Pre-test and Post-test Design method). Result: Doodle Art 3D is feasible as an effort to reduce patient anxiety in health service facility. Doodle ART 3d is effective toward reducing the level of patient anxiety in health care. Conclusion: Doodle Art 3D is effective in reducing the level of patient’s anxiety viewed from the average difference of 0.50 compared to the control group. Doodle Art 3D.